Pengaruh Profitabilias, Kebijakan Dividen & Pertumbuhan Perusahaan terhadap Nilai Perusahaan dengan KDKI Sebagai Variabel Moderasi: (Studi pada Perusahaan LQ45 di BEI Periode 2021-2024) - Farista Damayanti; Supami Wahyu Setiyowati; Ati Retna Sari (AKUNTANSI 45, 2026)
This study is designed to evaluate the impact of profitability (ROA), dividend policy (DPR), and corporate expansion on company value (PBV), with the structure of the independent board of commissioners serving as a moderator. Enterprise value reflects investors' perceptions of a company's future potential, which is influenced by financial performance and corporate governance practices. Profitability indicates an entity's capacity to generate profits, dividend policy reflects the strategy for distributing profits to shareholders, and company growth indicates the prospect of improved performance in the future. On the other hand, independent board members play a crucial role in the oversight system to ensure that management actions are in line with the interests of shareholders. This study uses a quantitative method with a sample of companies listed on the LQ45 index on the Indonesia Stock Exchange during the 2021-2024 period. The sample selection was conducted using purposive sampling. Secondary data were obtained from published annual financial reports and corporate governance reports through the official IDX website. The data analysis methods applied include multiple linear regression analysis and Moderated Regression Analysis (MRA) to evaluate the moderation function.